2019
DOI: 10.3389/fpls.2019.01316
|View full text |Cite
|
Sign up to set email alerts
|

Legumes Modulate Allocation to Rhizobial Nitrogen Fixation in Response to Factorial Light and Nitrogen Manipulation

Abstract: The costs and benefits that define gain from trade in resource mutualisms depend on resource availability. Optimal partitioning theory predicts that allocation to direct uptake versus trade will be determined by both the relative benefit of the resource acquired through trade and the relative cost of the resource being traded away. While the costs and benefits of carbon:nitrogen exchange in the legume–rhizobia symbiosis have been examined in depth with regards to mineral nitrogen availability, the effects of v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(27 citation statements)
references
References 50 publications
0
26
1
Order By: Relevance
“…Three times higher microbial N 2 fixation rates and five times higher CH 4 oxidation rates in the presence of light indicate that these processes are strongly stimulated by photosynthesis, either directly or indirectly. For leguminous plant species it has recently been reported that the plants modulate their carbon allocation to symbiotic nitrogen-fixing Rhizobia in response to both light an N availability (Friel and Friesen 2019). For N 2 fixation associated with Sphagnum, it has been observed before that N 2 fixation rates are highest under illuminated conditions (Larmola et al 2014;van den Elzen et al 2017).…”
Section: Light As a Key Driver Of N 2 Fixationmentioning
confidence: 99%
“…Three times higher microbial N 2 fixation rates and five times higher CH 4 oxidation rates in the presence of light indicate that these processes are strongly stimulated by photosynthesis, either directly or indirectly. For leguminous plant species it has recently been reported that the plants modulate their carbon allocation to symbiotic nitrogen-fixing Rhizobia in response to both light an N availability (Friel and Friesen 2019). For N 2 fixation associated with Sphagnum, it has been observed before that N 2 fixation rates are highest under illuminated conditions (Larmola et al 2014;van den Elzen et al 2017).…”
Section: Light As a Key Driver Of N 2 Fixationmentioning
confidence: 99%
“…Gibert et al., 2019). This rhizobia–legume interaction strongly depends on the environment (Araújo et al., 2015; Batstone et al., 2020; Heath et al., 2010; Rehling et al., 2019; Zahran, 1999), but is particularly beneficial at high light, but low nutrient conditions (Friel & Friesen, 2019; Lau et al., 2012; Taylor & Menge, 2018). Second, the life span of a plant represents a trade‐off between survival and reproduction (Friedman, 2020) that affects its biomass allocation and response to different environments (Eziz et al., 2017; Husáková et al., 2018; Poorter et al., 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the severity of sanctions –the relative fitness between sanctioned and unsanctioned nodules–could depend on environmental conditions, such as fertilizer nitrogen in the soil, to which even legume crops are often exposed because of carry‐over from previous nonfixing crops. When soil nitrogen increases, legumes typically allocate fewer resources toward the symbiosis (Streeter & Wong, 1988; Denison & Harter, 1995; Fujikake et al., 2002; Friel & Friesen, 2019), although there are exceptions among legume species (Regus et al, 2014). But we understand less about the extent to which plants are capable of preferentially allocating resources to reflect the relative performance of each effective nodule on the same plant, sometimes called “relative sanctions” (West, Kiers, Simms, & Denison, 2002), which will play a large role in the evolutionary maintenance of the mutualism in today's changing terrestrial ecosystem.…”
Section: Introductionmentioning
confidence: 99%